Pentapartitioned Neutrosophic Pythagorean Connectedness - R. Radha; Annapoorna M S, S. Vasundhara; Parul Arora; Ankita Tiwari; R.Prema (Neutrosophic Sets and Systems)
The aim of this paper is to introduce the concept of Pentapartitioned Neutrosophic Pythagorean [PNP] connectedness is introduced and its properties are also studied. Also we investigate some interrelations between these types of Pentapartitioned Neutrosophic Pythagorean connectedness. We show that the continuous image of Pentapartitioned Neutrosophic Pythagorean connected space is PNP connected.